Dengue in the campus community of an overseas American university: A cross-sectional study - Mohammed, Hamish; Hayden, Mary H; Lee, Elise; Santiago, Luis M; Krecek, Rosina C; Revan, Floyd; Hunsperger, Elizabeth (The Journal of Infection in Developing Countries, 2019)
Introduction: After a large outbreak of dengue virus (DENV) serotype-3 in Saint Kitts and Nevis (SKN) in 2008, we performed a cross-sectional study to determine the prevalence of anti-DENV immunoglobulin G (IgG) antibodies in expatriate and local persons affiliated with an American veterinary school there. Methodology: This campus community comprised mostly expatriate students and faculty and Kittitian administrative staff. In 2009, a stratified random sample of students, faculty and staff was invited to complete an electronic survey to assess risk factors for DENV and provide blood for testing for anti-DENV IgG antibodies by an enzyme-linked immunosorbent assay. IgG-positive specimens were also tested by a 90% plaque reduction neutralization test (PRNT90) to determine immunoreactivity to DENV (1-4) serotypes and West Nile virus. Risk factors for anti-DENV IgG seropositivity were determined using simple and adjusted logistic regression. Results: Of the 118 participants, the overall prevalence of DENV IgG antibodies was 44.1% (95% confidence interval [CI]: 35.1-53.0%), ranging from 30.1% in students, 100.0% in staff and 57.9% in faculty (p < 0.001). Duration of residence in St. Kitts was the only variable significantly associated with seropositivity on multiple logistic regression (adjusted odds ratio [95% CI]: 1.21 [1.07-1.37]). The serotype of DENV was determined in 11 persons: DENV-1 (n = 4), DENV-2 (n = 3), and DENV-3 (n = 4). Conclusions: Expatriate students and faculty moving to St. Kitts from non-endemic areas were at high risk of DENV infection. There is a need for increased emphasis on pre-travel mosquito-borne virus prevention education for persons moving to St. Kitts to study and work.